Ceramic green body prepared from high-content tailings, high-strength ceramic tile and preparation methods of ceramic green body and high-strength ceramic tile
By adding red mud and vanadium titanium slag to ceramic blanks, replacing the traditional high-aluminum blank formulations, reducing the firing temperature and cycle, the resource waste and environmental pollution of vanadium titanium slag and red mud are solved, and high strength is achieved Production of ceramic tiles.
Patent Information
- Application Number
- CN202411384483.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing technology fails to effectively utilize vanadium titanium slag and red mud, resulting in waste of resources and environmental pollution, and the ceramic industry faces the problem of raw materials shortage.
Ceramic blanks prepared with high-addition tailings are prepared by reasonably proportioning red mud and vanadium titanium slag, replacing the traditional high-aluminum reinforced blank formulation system, reducing the firing temperature and shortening the firing cycle, and preparing high-strength ceramic tiles.
It solves the harm caused by the stacking of vanadium titanium slag and red mud to the natural ecology and environment, realizes the rational use of resources, reduces the production cost of ceramic products, and improves the strength and firing efficiency of the products.
Smart Images

Figure CN119241211A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to a ceramic body prepared with high-doped tailings, a high-strength ceramic brick and a preparation method. Background Art
[0002] With the rapid development of economy and construction industry, people's living standards are constantly improving, and the ceramic industry has developed rapidly. However, due to the excessive exploitation and unreasonable use of mineral resources in the ceramic industry, high-quality ceramic raw materials are becoming less and less, which directly or indirectly affects the sustainable development of the ceramic industry itself. Therefore, how to use low-quality raw materials to produce high-quality ceramic tiles has become an urgent problem that the industry needs to solve.
[0003] At the same time, ironmaking will discharge a large amount of vanadium-titanium slag. According to relevant data, every ton of iron smelting can produce about 0.3 to 1 ton of waste slag. The lower the ore grade, the greater the slag discharge. Due to the high vanadium-titanium slag content, it cannot be directly used to produce slag silicate cement; and because its titanium grade is not high enough, it cannot be used as a raw material for the titanium industry. Therefore, a large amount of vanadium-titanium slag cannot be reasonably utilized, which not only causes a waste of resources, occupies a huge area of the yard, but also pollutes the environment.
[0004] In addition, red mud is an alkaline leaching waste discharged from the process of extracting alumina from bauxite, and is a typical solid waste in the aluminum industry. For every ton of alumina produced, 0.7 to 2.0 tons of red mud will be left. At present, the largest output is Bayer red mud, and the main treatment method is landfill or stockpiling, which occupies a lot of land on the one hand and causes serious environmental problems on the other hand, such as soil pollution, groundwater pollution and increased dust content in the air.
[0005] Therefore, the prior art has defects and needs to be improved and developed. Summary of the invention
[0006] The technical problem to be solved by the present invention is that, in view of the above-mentioned defects of the prior art, a ceramic body prepared with high-doped tailings, a high-strength ceramic brick and a preparation method thereof are provided, aiming to solve the problem that vanadium-titanium slag and red mud are not reasonably utilized in the prior art.
[0007] The technical solution adopted by the present invention to solve the technical problem is as follows:
[0008] In a first aspect, an embodiment of the present application provides a ceramic body prepared by high-doped tailings, wherein the raw materials of the ceramic body include, by weight:
[0009] 20-30 parts of red mud, 0-8 parts of bentonite, 65-70 parts of vanadium-titanium slag, 0-10 parts of ball clay, and 0.3-0.5 parts of green body degumming agent.
[0010] Optionally, in one embodiment of the present application, the chemical components of the ceramic body include, by weight:
[0011] SiO2 25-35 parts, Al2O3 10-13 parts, K2O 0.1-0.5 parts, Na2O 1.5-4.5 parts, CaO 1.5-3.5 parts, MgO 1.5-2.5 parts, TiO2 5.5-9.45 parts, Fe2O3 25.5-35.5 parts, Cr2O3 2.1-3.1 parts, MnO 4.2-6.3 parts.
[0012] Optionally, in one embodiment of the present application, the chemical components of the red mud include, by weight percentage:
[0013] Loss on ignition 8.25~11.56%, Al2O3 18.5~22.56%, SiO2 12.5~18.5%, Fe2O330.5~39.47%, CaO 4.5~6.5%, MgO 0.1~0.5%, K2O 0.1~0.75%, Na2O5.5~7.9%, TiO2 2.95~5.5%.
[0014] Optionally, in one embodiment of the present application, the chemical components of the vanadium-titanium slag include, by weight percentage:
[0015] Ignition reduction 1.16~1.55%, Al2O3 3.5~4.56%, SiO2 12.55~18.05%, Fe2O342.65~49.47%, CaO 2.05~3.71%, MgO 2.5~3.55%, K2O 0.01~0.05%, Na2O3.55~5.91%, TiO2 8.95~12.25%, MnO 7.85~11.58%, Cr2O3 2.35~5.51%.
[0016] The present invention also provides a high-strength ceramic tile, comprising: the ceramic body as described above, a base glaze layer arranged on the ceramic body, a pattern decoration layer arranged on the base glaze layer, and a surface glaze layer arranged on the pattern decoration layer.
[0017] Optionally, in one embodiment of the present application, the raw materials of the base glaze layer include, by weight:
[0018] 5-10 parts of kaolin, 10-15 parts of quartz, 50-60 parts of albite, 10-15 parts of potassium feldspar, 1-5 parts of calcined talc, 0-5 parts of zirconium silicate, 2-8 parts of calcite, 0.3-0.5 parts of sodium tripolyphosphate, and 0.1-0.2 parts of carboxymethyl cellulose.
[0019] Optionally, in one embodiment of the present application, the chemical components of the base glaze layer include, by weight percentage:
[0020] SiO2 55~60%, Al2O3 15~25%, Na2O 5~8%, K2O 1.5~2.5%, CaO 1~5%, MgO0.5~1.5%, ZrO2 0.1~0.5%, Fe2O3 0.15~0.3%.
[0021] Optionally, in one embodiment of the present application, the raw materials of the glaze layer include, by weight:
[0022] 20-30 parts of frit, 5-12 parts of kaolin, 1-3 parts of calcined kaolin, 5-10 parts of quartz, 2-8 parts of barium carbonate, 25-38 parts of albite, 5-8 parts of calcite, 3-9 parts of calcined talc, 3-5 parts of zinc oxide, 0.3-0.5 parts of sodium tripolyphosphate, and 0.1-0.2 parts of carboxymethyl cellulose.
[0023] Optionally, in one embodiment of the present application, the chemical components of the glaze layer include, by weight percentage:
[0024] SiO2 45.5~58.89%, Al2O3 10.5~15.8%, K2O 1.05~1.82%, Na2O3.5~5.44%, CaO 5.5~8.85%, MgO 0.5~3.84%, Fe2O3 0.1~0.36%, B2O30.1~3.25%, BaO 5.5~8.67%, ZnO 4.35~6.72%;
[0025] The chemical components of the frit include, by weight percentage:
[0026] SiO2 45.5~55.72%, Al2O3 5.0~10.5%, K2O 0.35~3.25%, Na2O3.85~8.45%, CaO 7.5~12.5%, MgO 0.59~3.85%, Fe2O3 0.1~0.25%, B2O32.5~5.55%, BaO 7.5~12.55%, ZnO 10.55~15.52%.
[0027] The present invention also provides a method for preparing the high-strength ceramic brick as described above, comprising:
[0028] Mix and grind 20-30 parts of red mud, 0-8 parts of bentonite, 65-70 parts of vanadium-titanium slag, 0-10 parts of ball clay, and 0.3-0.5 parts of green body disintegrator to obtain a formula slurry that meets the preset fineness;
[0029] The formula slurry is sieved, aged, and impurity removed, and then spray-dried to obtain a powder;
[0030] The powder is pressed into a shape, dried in a drying kiln to obtain a ceramic body, and a base glaze is applied on the ceramic body to obtain a base glaze layer;
[0031] Performing inkjet decoration on the base glaze layer to obtain a pattern decoration layer, applying a top glaze on the pattern decoration layer to obtain the top glaze layer and then drying to obtain a glaze blank;
[0032] The glaze blank is fired at a firing temperature of 1050° C. to 1080° C. and a firing period of 35 to 45 minutes to obtain a high-strength ceramic tile.
[0033] The present invention discloses a ceramic body prepared by high-doped tailings, a high-strength ceramic brick and a preparation method, wherein the raw materials of the ceramic body include, by weight, 20-30 parts of red mud, 0-8 parts of bentonite, 65-70 parts of vanadium-titanium slag, 0-10 parts of ball clay, and 0.3-0.5 parts of a body disintegrator. The present invention replaces the traditional body formula system using high aluminum reinforcement by adding a large amount of two low-quality raw materials, red mud and vanadium-titanium slag, through reasonable proportion, greatly reducing the firing temperature of ceramic products and shortening the firing cycle, not only solving the huge harm to the natural ecology and environment caused by the stacking of red mud and vanadium-titanium slag, but also making more reasonable use of red mud and vanadium-titanium slag. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a flow chart of a preferred embodiment of a method for preparing high-strength ceramic bricks in the present invention.
[0035] Figure 2 It is a specific production process flow chart for preparing high-strength ceramic bricks in the present invention. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the present invention clearer and more specific, the present invention is further described in detail below with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0037] The building ceramics industry produces about 10 billion square meters of ceramic tiles every year, which consumes 300 million tons of mineral raw materials and is currently facing a shortage of raw materials. The present invention provides a Fe2O3-MnO-CaO-MgO-SiO2-Al2O3 ceramic blank formulation system developed using iron slag, breaking the traditional Na2O-K2O-SiO2-Al2O3 blank formulation system, and forming a special ceramic blank formulation system by replacing part of the clay with red mud, replacing potassium-sodium feldspar and ceramic flux raw materials with vanadium-titanium slag, and preparing ceramic products with special properties, so as to promote the rational utilization of red mud resources, and combining vanadium-titanium slag to replace potassium-sodium feldspar and flux raw materials in ceramic raw materials, so as to promote the rational utilization of vanadium-titanium slag resources.
[0038] The present invention provides a ceramic body prepared by high-doped tailings, wherein the raw materials of the ceramic body include, by weight:
[0039] 20-30 parts of red mud, 0-8 parts of bentonite, 65-70 parts of vanadium-titanium slag, 0-10 parts of ball clay, and 0.3-0.5 parts of green body degumming agent.
[0040] Specifically, the green body disintegrator may include one or more of sodium tripolyphosphate, a diluent, sodium humate, and water glass. The Fe2O3, CaO, MgO, Cr2O3, MnO, TiO2, and Na2O contained in the red mud and vanadium-titanium slag in the ceramic formula raw materials of the present invention are combined with a small amount of clay to form a low-temperature fast-firing green body system during the firing process. Due to the high mixing ratio of red mud and vanadium-titanium slag, the red mud and vanadium-titanium slag need to be homogenized before batching, and multi-point sampling and component analysis are performed.
[0041] The present invention adopts red mud and vanadium-titanium slag, two low-quality raw materials, and replaces the traditional high-aluminum reinforced green body formula system through reasonable proportioning, adds less than 10% of clay raw materials, and develops a low-aluminum high-strength green body formula system, the product performance of which reaches the national standard of ceramic products, and the firing temperature range is 1050°C to 1080°C, which greatly reduces the firing temperature of ceramic products and shortens the firing cycle. Therefore, not only the huge harm caused by the stacking of red mud and vanadium-titanium slag to the natural ecology and environment is solved, but also the recycling of red mud and vanadium-titanium slag makes the mineral resources more reasonably utilized.
[0042] In one embodiment, the raw materials of the ceramic body include, by weight: 22 parts of red mud, 8 parts of bentonite, 70 parts of vanadium-titanium slag, 0.3 parts of sodium tripolyphosphate, and 0.1 parts of carboxymethyl cellulose (CMC).
[0043] In one implementation of the present invention, the chemical components of the ceramic body include, by weight:
[0044] SiO2 25-35 parts, Al2O3 10-13 parts, K2O 0.1-0.5 parts, Na2O 1.5-4.5 parts, CaO 1.5-3.5 parts, MgO 1.5-2.5 parts, TiO2 5.5-9.45 parts, Fe2O3 25.5-35.5 parts, Cr2O3 2.1-3.1 parts, MnO 4.2-6.3 parts.
[0045] Specifically, based on the characteristics of vanadium-titanium slag and red mud ore, which are low in aluminum and silicon and rich in fluxing components such as sodium, calcium, and magnesium commonly used in traditional green bodies, the formula can be quickly sintered at 1050°C to 1080°C through the action of non-alkaline earth metal oxides and alkaline earth metal oxide composite low-temperature fluxes to obtain ceramic products that meet the performance standards. The product has a water absorption rate of less than 0.1, a modulus of rupture of 55 to 68 MPa, a firing range of above 30°C, and a firing cycle of 35min to 45min.
[0046] In one implementation of the present invention, the chemical components of the red mud, measured by weight percentage, include:
[0047] Loss on ignition 8.25~11.56%, Al2O3 18.5~22.56%, SiO2 12.5~18.5%, Fe2O330.5~39.47%, CaO 4.5~6.5%, MgO 0.1~0.5%, K2O 0.1~0.75%, Na2O5.5~7.9%, TiO2 2.95~5.5%.
[0048] Specifically, red mud is mainly composed of hematite (Fe2O3), sodium titanium oxide (Na4Ti5O2, Na2TiO3), anhydrous sodium sulfate (Na2SO4), calcium aluminum stone (Ca2Al2SiO7), siliceous rock (Ca3Al2(SiO2)(OH)8); clay is mainly composed of quartz, magnesium-containing ferrosilicon ore, calcite and muscovite, and muscovite mixed with appropriate water can exert the plasticity of clay. The Ca and Mg content in red mud is conducive to the formation of diopside phase, and the high Ca content is conducive to the formation of calcium feldspar phase, which is conducive to the solidification of sodium elements brought by red mud, and then the formation of sodium-containing calcium feldspar, which promotes the densification process and is conducive to the formation of a dense structure of the sample. Therefore, it can replace part of the clay. In the range of 290-400℃, the mass loss of dry red mud is 9.46%, which is derived from the volatilization of chemically bound water; in the range of 620-750℃, the mass loss of dry clay is 8.52%, which is mainly derived from the release of CO2 during the decomposition of calcite. The sintering process after mixing is similar to that of the green body, and CO2 is released at about 720℃. The content of released CO2 increases with the increase of clay addition. The main crystal phases of red mud and clay after high-temperature sintering are pyroxene phase and calcium feldspar (CaAl2Si2O8). With the increase of red mud content (the decrease of clay content), the quartz content decreases, which is consistent with the quartz content in clay. The pyroxene phase first increases and then slightly decreases, especially diopside (CaMgSi2O6). When the content of Ca and Mg elements is high, it is more conducive to the formation of diopside. When calcium feldspar and pyroxene are the main crystal phases, especially the high proportion of diopside in pyroxene, it is beneficial to improve the strength of ceramic products.
[0049] In one implementation of the present invention, the chemical components of the vanadium-titanium slag, measured by weight percentage, include:
[0050] Ignition reduction 1.16~1.55%, Al2O3 3.5~4.56%, SiO2 12.55~18.05%, Fe2O342.65~49.47%, CaO 2.05~3.71%, MgO 2.5~3.55%, K2O 0.01~0.05%, Na2O3.55~5.91%, TiO2 8.95~12.25%, MnO 7.85~11.58%, Cr2O3 2.35~5.51%.
[0051] Specifically, vanadium-titanium slag is rich in metal oxides, and its introduction into the green body formula can greatly improve the strength of the product. Its main crystal phases at high temperatures are hematite (Fe2O3), hematite (containing chromium) (Fe 0.6 Cr 0.4 )2O3, ferromanganese spinel MnFe2O4, ilmenite Fe +2 TiO3, ferromagnesian tantalum (Mg, Fe) (Ti3Fe)O10 、Centrovanadium titanium ore V2 +3 Ti3O9 and a small amount of rutile TiO2. Red mud and vanadium-titanium slag have high iron content, and their main crystal phase is hematite. The high iron, calcium, magnesium and sodium flux in the composition provide favorable conditions for low-temperature fast firing, and the firing temperature can be reduced to 1050℃~1080℃.
[0052] The present invention utilizes red mud and vanadium-titanium slag containing rich Fe2O3, MnO, TiO2, Cr2O3 and other metal oxides, combined with SiO2, Al2O3, Na2O, MgO and CaO in the blank system to jointly construct a high-strength ceramic formula system, the maximum rupture modulus of which can reach 58-68MPa. The rupture modulus of traditional ceramic products is 45MPa, which greatly improves the rupture modulus index of ceramic products.
[0053] The present invention also provides a high-strength ceramic tile, which includes: the ceramic body as described above, a base glaze layer arranged on the ceramic body, a pattern decoration layer arranged on the base glaze layer, and a surface glaze layer arranged on the pattern decoration layer.
[0054] The firing temperature of the high-strength ceramic brick of the present invention is lower than 1080°C. Since the ceramic body is made by replacing most of the clay with red mud and replacing the ceramic barren raw materials with vanadium-titanium slag, the product rupture modulus reaches 58-68MPa. Specifically, red mud is added to the formula of the ceramic body, combined with less than 10% of clay, so that the forming strength and dry billet strength of the body meet the production requirements; vanadium-titanium slag is the main raw material of the billet, which directly affects the billet firing temperature and product strength. Therefore, the stability of the raw material is extremely important, and it needs to be repeatedly homogenized and multi-point sampling for component analysis. Only after meeting the standards can it be used in the billet formula feeding production. The formula is designed by utilizing the rich Fe2O3, MnO, TiO2, Cr2O3 and other metal oxides in red mud and vanadium-titanium slag, combined with SiO2, Al2O3, Na2O, MgO and CaO in the blank system to jointly construct a low-aluminum and high-strength ceramic formula system. After the ceramic blank is obtained, a base glaze, pattern decoration and surface glaze are applied to obtain a ceramic product with a short firing cycle, a wide firing range, easy control of kiln firing and high strength.
[0055] In one implementation of the present invention, since the blank structure mainly introduces metal oxides into vanadium-titanium slag and red mud, and forms a low-temperature blank system with alkaline earth metal oxides, SiO2 and Al2O3 in the blank react with metal oxides in vanadium-titanium slag to generate mullite, calcium feldspar and pyroxene as main crystal phases. Complex decomposition reactions occur during high-temperature firing. In order to avoid the high-temperature exhaust gas affecting the bonding of the blank and glaze and the quality of the glaze, a matching low-temperature base glaze formula is developed. The raw materials of the base glaze layer include, by weight:
[0056] 5-10 parts of kaolin, 10-15 parts of quartz, 50-60 parts of albite, 10-15 parts of potassium feldspar, 1-5 parts of calcined talc, 0-5 parts of zirconium silicate, 2-8 parts of calcite, 0.3-0.5 parts of sodium tripolyphosphate, and 0.1-0.2 parts of carboxymethyl cellulose.
[0057] Specifically, the base glaze specific gravity of the base glaze layer is controlled to be 1.65-1.70 g / cm 3 The glaze amount (300X300mm specification plate) is 35-40g, the glaze slurry fineness is controlled to be 0.6-1.2% (325 mesh sieve residue), and the glossiness after calcination is not greater than 8°. The base glaze provided in the embodiment of the present application has the process properties of large glaze amount and high high temperature viscosity, which can minimize the defects such as pinholes and melt holes caused by the upward escape of gas decomposed from the green body during the sintering process.
[0058] In one implementation of the present invention, the chemical components of the base glaze layer include, by weight percentage:
[0059] SiO2 55~60%, Al2O3 15~25%, Na2O 5~8%, K2O 1.5~2.5%, CaO 1~5%, MgO0.5~1.5%, ZrO2 0.1~0.5%, Fe2O3 0.15~0.3%.
[0060] In one implementation of the present invention, due to the characteristics of the formula of the present invention, red mud and vanadium-titanium slag undergo complex decomposition reactions at high temperatures, in order to avoid exhaust at high temperatures affecting the body glaze combination and glaze surface quality, a matching low-temperature glaze formula is developed. The raw materials of the glaze layer include, by weight:
[0061] 20-30 parts of frit, 5-12 parts of kaolin, 1-3 parts of calcined kaolin, 5-10 parts of quartz, 2-8 parts of barium carbonate, 25-38 parts of albite, 5-8 parts of calcite, 3-9 parts of calcined talc, 3-5 parts of zinc oxide, 0.3-0.5 parts of sodium tripolyphosphate, and 0.1-0.2 parts of carboxymethyl cellulose.
[0062] The above glaze specific gravity is controlled to be 1.6~1.65g / cm 3 The glaze amount (300×300mm specification plate) is 20~25g, the glaze slurry fineness is controlled to be 0.3~0.5% (325 mesh sieve residue), and it is sintered at a temperature of 1050℃~1080℃ to obtain a polished tile with a smooth glaze surface, high transparency, and a glossiness of 25~35°. The Mohs hardness of the product after polishing reaches 3~5.
[0063] The glaze provided in the embodiment of the present application can avoid exhaust at high temperature affecting the bonding of the body and glaze and the quality of the glaze surface.
[0064] In one implementation of the present invention, the chemical components of the glaze layer, measured by weight percentage, include:
[0065] SiO2 45.5~58.89%, Al2O3 10.5~15.8%, K2O 1.05~1.82%, Na2O3.5~5.44%, CaO 5.5~8.85%, MgO 0.5~3.84%, Fe2O3 0.1~0.36%, B2O30.1~3.25%, BaO 5.5~8.67%, ZnO 4.35~6.72%.
[0066] The chemical components of the frit include, by weight percentage:
[0067] SiO2 45.5~55.72%, Al2O3 5.0~10.5%, K2O 0.35~3.25%, Na2O3.85~8.45%, CaO 7.5~12.5%, MgO 0.59~3.85%, Fe2O3 0.1~0.25%, B2O32.5~5.55%, BaO 7.5~12.55%, ZnO 10.55~15.52%.
[0068] Specifically, the chemical components of the glaze layer, measured by weight percentage, include: SiO2 54.52%, Al2O3 14.02%, K2O 1.42%, Na2O 4.44%, CaO 6.85%, MgO 0.84%, Fe2O3 0.16%, B2O3 0.35%, BaO 6.17%, ZnO 5.42%, and loss on ignition 5.81%; the chemical components of the frit, measured by weight percentage, include: SiO2 52.17%, Al2O3 5.19%, K2O 0.48%, Na2O 4.85%, CaO 9.02%, MgO 1.82%, Fe2O3 0.12%, B2O3 2.88%, BaO 8.22%, ZnO 14.16%, and loss on ignition 1.09%.
[0069] The present invention also provides a method for preparing the high-strength ceramic brick as described above, Figure 1 As shown, the preparation method of the high-strength ceramic brick comprises:
[0070] Step S100, mixing and grinding 20-30 parts of red mud, 0-8 parts of bentonite, 65-70 parts of vanadium-titanium slag, 0-10 parts of ball clay, and 0.3-0.5 parts of green body disintegrator to obtain a formula slurry meeting a preset fineness;
[0071] Step S200, sieving, aging, and removing impurities from the formula slurry, and then spray drying to obtain a powder;
[0072] Step S300, pressing the powder into a shape, drying it in a drying kiln to obtain a ceramic body, and applying a base glaze on the ceramic body to obtain a base glaze layer;
[0073] Step S400, performing inkjet decoration on the base glaze layer to obtain a pattern decoration layer, applying a top glaze on the pattern decoration layer to obtain the top glaze layer and then drying to obtain a glaze blank;
[0074] Step S500, firing the glaze blank at a firing temperature of 1050°C to 1080°C and a firing period of 35 to 45 minutes to obtain a high-strength ceramic tile.
[0075] like Figure 2 As shown, the embodiment of the present application first processes the raw materials of red mud and vanadium-titanium slag. Due to the high mixing ratio of red mud and vanadium-titanium slag, the red mud and vanadium-titanium slag need to be homogenized before mixing, and multi-point sampling and component analysis are performed. The raw materials in the formula components are aged and homogenized, and then fed into a ball mill through a feeder according to the formula ratio to obtain a formula slurry that meets the fineness requirements. The slurry is sieved, aged, and impurities are removed, and then spray-dried to obtain a powder, and then the powder is pressed into shape (the modulus of rupture reaches 0.6-0.8MPa), and dried in a drying kiln (the modulus of rupture reaches 1.2MPa-1.5MPa) to obtain a ceramic body; on the ceramic body with a certain strength after drying, after cleaning the surface, apply the bottom glaze, inkjet (decorative pattern), and apply the surface glaze to dry, control the moisture of the body entering the kiln, and obtain the decorated glaze blank, so that all the process flows before entering the firing kiln are completed. The decorated glaze blanks are sent to the roller kiln for firing at a temperature of 1050℃~1080℃ and a firing cycle of 35~45min. The products out of the kiln are edged, chamfered, air-dried, inspected, color-separated, graded, and then packaged and stored. The water absorption rate of the finished products is less than 0.1%.
[0076] Specifically, the raw materials are aged and homogenized, and are hard raw materials. They need to be crushed before batching to improve the efficiency and accuracy of wet ball milling. The coarse crushing fineness of the raw materials is controlled to be d50<3mm. According to the moisture content of each raw material and the percentage of each raw material in the formula design, a belt batcher is used to accurately transport the prepared raw materials into the ball mill. The raw materials are powdered by wet ball milling and spray drying processes, and then dry pressed to obtain ceramic green bodies. In one embodiment, the wet ball milling fineness of the high-strength ceramic tile blank slurry is controlled to have a 250-mesh sieve residue of 1.8% to 2.5%, and the moisture content of the powder is controlled to be 7.5 to 8.5%.
[0077] In this way, the present invention solves the problem that the ceramic industry only applies red mud or vanadium-titanium slag to the fields of foamed ceramics, porous ceramics, and cement. Even if it is applied to low-absorption ceramics, it only uses the coloring function of vanadium-titanium slag and red mud, and the mixing ratio is low. Through this blank system, the proportion of vanadium-titanium slag and red mud in the blank formula is further increased, among which the mixing ratio of vanadium-titanium slag can reach 55% to 70%, and the mixing ratio of red mud can reach 20% to 30%. The traditional formula adopts a high-aluminum reinforced blank formula system. The traditional blank clay dosage is generally 18% to 35%, while the clay dosage of this blank system is 5% to 10%, which greatly reduces the amount of clay used in the blank formula. The present invention has established a low-aluminum and high-strength blank formula system based on metal oxides, and the other properties of its products have reached the national standards for traditional ceramic products. The blank system of the present invention forms a low-temperature blank formula system by adding 55% to 70% vanadium-titanium slag and 20% to 30% red mud, combined with the low-temperature flux contained in the blank system, which greatly reduces the firing temperature and shortens the firing time, expands the firing range and stabilizes the product performance. The blank formula of high-vanadium-titanium slag and red mud forms a low-temperature blank system by combining non-alkaline earth metal oxides and alkaline earth metal oxides, which greatly improves the modulus of rupture of the product and can reach 58 to 68 MPa. A large amount of vanadium-titanium slag and red mud are introduced into the ceramic blank, and a low-temperature blank system is formed by composite fluxing to prepare low-temperature fast-firing blanks, which greatly reduces the total energy consumption, increases the service life of kilns and kiln tools, achieves energy conservation and emission reduction, and greatly reduces the cost of ceramic production.
[0078] Specific embodiments are listed below for illustration.
[0079] Embodiment 1
[0080] The blank formulation of this embodiment is as follows according to weight percentage:
[0081] 5 parts of bentonite, 4.6 parts of ball clay, 25 parts of red mud, 65 parts of vanadium-titanium slag, 0.3 parts of sodium tripolyphosphate, and 0.1 parts of carboxymethyl cellulose (CMC).
[0082] The chemical composition of the above-mentioned green body formula includes by weight percentage:
[0083] SiO2 19.35%, Al2O3 14.1%, K2O 0.59%, Na2O 4.92%, CaO 3.17%, MgO 2.08%, TiO2 6.12%, Fe2O3 37.37%, Cr2O3 2.94%, MnO 6.23%, ignition loss 3.13%.
[0084] This embodiment adopts a low-temperature fast-firing process, with a firing temperature of 1080° C. and a firing time of 35 min. The obtained product has a water absorption rate of 0.04% and a modulus of rupture of 66 Mpa.
[0085] This embodiment includes the following production steps:
[0086] Step A1: The raw materials are aged and homogenized. They are hard raw materials and need to be crushed before mixing to improve the efficiency and accuracy of wet ball milling. The coarse crushing fineness of the raw materials is controlled to be d50<3mm;
[0087] Step A2, batching, according to the moisture content of each raw material and the percentage of each raw material in the formula design, use a belt batching machine to accurately convey the prepared raw materials into the ball mill;
[0088] Step A3, the raw materials are powdered by wet ball milling and spray drying process and then dry pressed to obtain ceramic green body, wherein the wet ball milling fineness of the ceramic tile green body slurry is controlled to be 2.0% of the 250 mesh sieve residue, and the moisture content of the powder is controlled to be 7.5-8.5%;
[0089] Step A4: After the ceramic green body is dried, a base glaze is applied, and after being decorated by a digital inkjet machine, it becomes an overglaze colored body. Then, a bell jar or a glaze spraying device is used to apply a top glaze on the green body, and the glaze is applied by a glaze throwing process.
[0090] Due to the characteristics of the formula, vanadium-titanium slag and red mud will undergo complex decomposition reactions at high temperatures. In order to avoid the high-temperature exhaust gas affecting the body glaze combination and glaze quality, a matching low-temperature base glaze formula was developed. The raw materials of the base glaze include, by weight:
[0091] 8 parts of kaolin, 12 parts of quartz, 55 parts of albite, 14 parts of potassium feldspar, 4 parts of calcined talc, 3 parts of zirconium silicate, 5 parts of calcite, 0.4 parts of sodium tripolyphosphate, and 0.2 parts of carboxymethyl cellulose (CMC).
[0092] The chemical composition of the base glaze, measured by weight percentage, includes:
[0093] SiO2 58.47%, Al2O3 24%, Na2O 8%, K2O 2.4%, CaO 4%, MgO 1.3%, ZrO20.5%, Fe2O3 0.3%, loss on ignition 1.03%.
[0094] The above-mentioned base glaze specific gravity is controlled to be 1.65g / cm 3 The glaze amount (300×300mm specification plate) is 38g, the glaze slurry fineness is controlled to 0.8% (325 mesh sieve residue), and the glossiness after calcination is not more than 10°.
[0095] Due to the characteristics of this formula, vanadium-titanium slag will undergo complex decomposition reactions at high temperatures. In order to avoid the high-temperature exhaust gas affecting the body glaze combination and glaze quality, a matching low-temperature glaze formula was developed. The glaze includes the following by weight:
[0096] 26 parts of frit, 10 parts of kaolin, 2 parts of calcined kaolin, 7 parts of quartz, 5 parts of barium carbonate, 33 parts of albite, 6 parts of calcite, 8 parts of calcined talc, 4 parts of zinc oxide; 0.5 parts of sodium tripolyphosphate, and 0.1 parts of carboxymethyl cellulose (CMC).
[0097] The chemical composition of the glaze is composed of the following components by weight percentage:
[0098] SiO2 54.52%, Al2O3 14.02%, K2O 1.42%, Na2O 4.44%, CaO 6.85%, MgO0.84%, Fe2O3 0.16%, B2O3 0.35%, BaO 6.17%, ZnO 5.42%, ignition loss 5.81%.
[0099] The chemical composition of the frit is composed of the following components by weight percentage:
[0100] SiO2 52.17%, Al2O3 5.19%, K2O 0.48%, Na2O 4.85%, CaO 9.02%, MgO 1.82%, Fe2O3 0.12%, B2O3 2.88%, BaO 8.22%, ZnO 14.16%, ignition loss 1.09%.
[0101] The glaze of this embodiment is made of transparent frit, and the glaze slurry fineness after processing is 0.4% (325 mesh sieve residue), and the glaze slurry specific gravity is controlled to be 1.65g / cm 3 The product glaze amount (300×300mm specification plate) is 25g.
[0102] Step A5, after the glaze process is completed, the green body is dried and then put into a roller kiln for firing at a temperature of 1080° C. for 35 minutes to produce a semi-finished product;
[0103] The glaze of this embodiment is sintered at a temperature of 1080°C to obtain a polished tile with a smooth glaze surface, high transparency, and a glossiness of 35°. The Mohs hardness of the product after polishing reaches 3 to 5.
[0104] Step A6: The semi-finished products of the fully polished type are edge-grinded, air-dried, inspected, color-separated, graded, and stored.
[0105] Embodiment 2
[0106] The blank formulation of this embodiment is as follows according to weight percentage:
[0107] 8 parts of bentonite, 22 parts of red mud, 70 parts of vanadium-titanium slag, 0.3 parts of sodium tripolyphosphate, and 0.1 parts of carboxymethyl cellulose (CMC).
[0108] The chemical composition of the above green body formula is composed of the following components by weight percentage:
[0109] SiO2 21.27%, Al2O3 8.9%, K2O 0.15%, Na2O 4.96%, CaO 3.13%, MgO2.21%, TiO2 8.12%, Fe2O3 38.51%, Cr2O3 3.16%, MnO 6.71%, ignition loss 2.88%.
[0110] This embodiment adopts a low-temperature fast-firing process, with a firing temperature of 1050° C. and a firing time of 35 min. The water absorption rate of the obtained product is 0.03%, and the flexural strength of the product is 68 MPa.
[0111] This embodiment includes the following production steps:
[0112] Step B1, the raw materials are aged and homogenized, and are hard raw materials. They need to be crushed before mixing to improve the efficiency and accuracy of wet ball milling. The coarse crushing fineness of the raw materials is controlled to be d50<3mm;
[0113] Step B2, batching, according to the moisture content of each raw material and the percentage of each raw material in the formula design, use a belt batching machine to accurately convey the prepared raw materials into the ball mill;
[0114] Step B3, the raw materials are powdered by wet ball milling and spray drying process and then dry pressed to obtain ceramic green body. Preferably, the wet ball milling fineness of the ceramic tile green body slurry is controlled to be 1.8% on a 250-mesh sieve, and the moisture content of the powder is controlled to be 7.5-8.5%;
[0115] Step B4: After the ceramic green body is dried, a base glaze is applied, and after being decorated by a digital inkjet machine, it becomes an overglaze colored body. Then, a bell jar or a glaze spraying device is used to apply a surface glaze on the green body, and the surface glaze adopts a glaze polishing process.
[0116] Due to the characteristics of the formula, vanadium-titanium slag and red mud will undergo complex decomposition reactions at high temperatures to produce gas. In order to avoid the high-temperature exhaust gas affecting the body glaze combination and glaze quality, a matching low-temperature base glaze formula was developed. The base glaze includes the following by weight:
[0117] 6 parts of kaolin, 14 parts of quartz, 58 parts of albite, 11 parts of potassium feldspar, 2 parts of calcined talc, 1 part of zirconium silicate, 6 parts of calcite, 0.5 parts of sodium tripolyphosphate, and 0.1 parts of carboxymethyl cellulose (CMC).
[0118] The chemical composition of the base glaze is composed of the following components by weight percentage:
[0119] SiO2 59.2%, Al2O3 20%, Na2O 7%, K2O 2.3%, CaO 3%, MgO 1.2%, ZrO2 0.3%, Fe2O3 0.2%, ignition loss 6.8%.
[0120] The above-mentioned base glaze specific gravity is controlled to be 1.60g / cm 3 The glaze amount (300×300mm specification plate) is 35g, the glaze slurry fineness is controlled to 0.6% (325 mesh sieve residue), and the glossiness after calcination is not more than 15°.
[0121] Due to the characteristics of the formula, vanadium-titanium slag and red mud will undergo complex decomposition reactions at high temperatures. In order to avoid the high-temperature exhaust gas affecting the body glaze combination and glaze quality, a matching low-temperature glaze formula was developed. The glaze includes the following by weight:
[0122] 29 parts of frit, 8 parts of kaolin, 3 parts of calcined kaolin, 10 parts of quartz, 7 parts of barium carbonate, 37 parts of albite, 8 parts of calcite, 4 parts of calcined talc, 3 parts of zinc oxide, 0.3 parts of sodium tripolyphosphate, and 0.2 parts of carboxymethyl cellulose (CMC).
[0123] The chemical composition of the glaze is composed of the following components by weight percentage:
[0124] SiO2 54.52%, Al2O3 14.02%, K2O 1.42%, Na2O 4.44%, CaO 6.85%, MgO0.84%, Fe2O3 0.16%, B2O3 0.35%, BaO 6.17%, ZnO 5.42%, ignition loss 5.81%.
[0125] The chemical composition of the frit is composed of the following components by weight percentage:
[0126] SiO2 52.17%, Al2O3 5.19%, K2O 0.48%, Na2O 4.85%, CaO 9.02%, MgO 1.82%, Fe2O3 0.12%, B2O3 2.88%, BaO 8.22%, ZnO 14.16%, ignition loss 1.09%.
[0127] The glaze of this embodiment is made of transparent frit, and the glaze slurry fineness after processing is 0.3% (325 mesh sieve residue), and the glaze slurry specific gravity is controlled to be 1.60g / cm 3 The product glaze amount (300×300mm specification plate) is 27g.
[0128] Step B5, after the glaze process is completed, the green body is dried and then put into a roller kiln for firing at a temperature of 1050° C. for 35 minutes to produce a semi-finished product;
[0129] The glaze of this embodiment is sintered at a temperature of 1050°C to obtain a polished tile with a smooth glaze surface, high transparency, and a glossiness of 25°. The Mohs hardness of the product after polishing reaches 3 to 5 levels;
[0130] Step B6: The fully polished semi-finished products out of the kiln are edge-grinded, air-dried, inspected, color-separated, graded, and stored.
[0131] The present invention provides a process for preparing a ceramic body with high-doped tailings. Through the action of a multi-element low-temperature flux, the formulation can be quickly sintered at 1060°C to 1100°C to obtain a ceramic product with performance standards. The product has a water absorption rate of less than 0.1, a rupture modulus of up to 75MPa, and a sintering range of more than 30°C.
[0132] The present invention achieves the following effects:
[0133] First, a large amount of vanadium-titanium slag is introduced into the blank, and the addition amount can reach 55% to 70%, which can completely replace the lean raw materials (such as potassium and sodium feldspar) in the blank; the introduction of red mud can reach 20% to 30%, which can replace most of the clay raw materials in the blank, so that the blank forming modulus of rupture reaches 0.65 to 0.75 MPa, and the dry blank modulus of rupture reaches 1.2 to 1.5 MPa, which meets the strength requirements of production and greatly slows down the depletion of high-quality mineral resources.
[0134] Secondly, the traditional formula of high-aluminum billet system with only clay to provide the body forming strength was changed to a low-aluminum billet system with low-quality raw materials of red mud and vanadium-titanium slag and reinforced with metal oxides, so that other performance of the product can meet the national standards of traditional ceramic products.
[0135] Third, the characteristics of the formula are that vanadium-titanium slag and red mud will undergo complex decomposition reactions at high temperatures. In order to avoid the high-temperature exhaust affecting the bonding of the body glaze and the quality of the glaze, a matching low-temperature base and surface glaze formula was developed.
[0136] Fourth, a large amount of vanadium-titanium slag and red mud are introduced into the green body. The sintering temperature of the green body can be greatly reduced by utilizing the characteristics of high iron content and the presence of Na2O, CaO, MgO, Fe2O3, MnO, etc. in the vanadium-titanium slag and red mud to form a multi-element low-temperature flux. The sintering temperature of the ceramic green body is reduced to 1050℃~1080℃, and the water absorption rate of the product is below 0.1. Compared with the sintering temperature of about 1180℃~1240℃ of the general ceramic green body formula, the sintering temperature of the present invention can be reduced by 130℃~160℃, the sintering temperature has been greatly reduced, and the firing cycle is also controlled at 35min, realizing a low-temperature and fast-firing ceramic production process and reducing the production cost of ceramic products.
[0137] Fifth, by utilizing the high iron oxide content in vanadium-titanium slag and red mud, combined with a special green body structure design of multiple low-temperature fluxes and polycrystalline phases, a low-aluminum and high-strength ceramic green body system is obtained. The maximum rupture modulus can reach 68MPa. The rupture modulus of traditional ceramic green bodies is 45MPa, which greatly improves the strength of ceramic products.
[0138] Sixth, by adding vanadium-titanium slag to the billet at a high level of 55% to 70% and red mud at a level of 20% to 30%, it helps vanadium-titanium and red mud mining companies solve the problem of slag digestion, improves the rational utilization rate of vanadium-titanium slag and red mud, eliminates the huge harm caused by vanadium-titanium slag and red mud to the natural ecology and environment, and realizes the green and environmental protection of mineral resources.
[0139] The present invention provides a ceramic body prepared with high-doped tailings, a high-strength ceramic brick and a preparation method, wherein the raw materials of the ceramic body include, by weight, 20-30 parts of red mud, 0-8 parts of bentonite, 65-70 parts of vanadium-titanium slag, 0-10 parts of ball clay, and 0.3-0.5 parts of a body disintegrator. The present invention replaces the traditional body formula system using high aluminum reinforcement by adding a large amount of two low-quality raw materials, red mud and vanadium-titanium slag, through reasonable proportion, greatly reducing the firing temperature of ceramic products and shortening the firing cycle, not only solving the huge harm to the natural ecology and environment caused by the stacking of red mud and vanadium-titanium slag, but also making more reasonable use of red mud and vanadium-titanium slag.
[0140] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A ceramic body prepared by high-doped tailings, characterized in that: The raw materials of the ceramic body include, by weight: 20-30 parts of red mud, 0-8 parts of bentonite, 65-70 parts of vanadium-titanium slag, 0-10 parts of ball clay, and 0.3-0.5 parts of green body degumming agent.
2. The ceramic body prepared from high-doped tailings according to claim 1, characterized in that: The chemical components of the ceramic body include, by weight: SiO2 25-35 parts, Al2O3 10-13 parts, K2O 0.1-0.5 parts, Na2O 1.5-4.5 parts, CaO 1.5-3.5 parts, MgO 1.5-2.5 parts, TiO2 5.5-9.45 parts, Fe2O3 25.5-35.5 parts, Cr2O3 2.1-3.1 parts, MnO 4.2-6.3 parts.
3. The ceramic body prepared from high-doped tailings according to claim 1, characterized in that: The chemical components of the red mud include, by weight percentage: Loss on ignition 8.25~11.56%, Al2O3 18.5~22.56%, SiO2 12.5~18.5%, Fe2O330.5~39.47%, CaO 4.5~6.5%, MgO 0.1~0.5%, K2O 0.1~0.75%, Na2O5.5~7.9%, TiO2 2.95~5.5%.
4. The ceramic body prepared from high-doped tailings according to claim 1, characterized in that: The chemical components of the vanadium-titanium slag include, by weight percentage: Ignition reduction 1.16~1.55%, Al2O3 3.5~4.56%, SiO2 12.55~18.05%, Fe2O342.65~49.47%, CaO 2.05~3.71%, MgO 2.5~3.55%, K2O 0.01~0.05%, Na2O3.55~5.91%, TiO2 8.95~12.25%, MnO 7.85~11.58%, Cr2O3 2.35~5.51%.
5. A high-strength ceramic brick, characterized in that: include: A ceramic body as described in any one of claims 1 to 4, a base glaze layer arranged on the ceramic body, a pattern decoration layer arranged on the base glaze layer, and a surface glaze layer arranged on the pattern decoration layer.
6. The high-strength ceramic brick according to claim 5, characterized in that: The raw materials of the base glaze layer include, by weight: 5-10 parts of kaolin, 10-15 parts of quartz, 50-60 parts of albite, 10-15 parts of potassium feldspar, 1-5 parts of calcined talc, 0-5 parts of zirconium silicate, 2-8 parts of calcite, 0.3-0.5 parts of sodium tripolyphosphate, and 0.1-0.2 parts of carboxymethyl cellulose.
7. The high-strength ceramic brick according to claim 5, characterized in that: The chemical components of the base glaze layer include, by weight percentage: SiO2 55~60%, Al2O3 15~25%, Na2O 5~8%, K2O 1.5~2.5%, CaO 1~5%, MgO 0.5~1.5%, ZrO2 0.1~0.5%, Fe2O3 0.15~0.3%.
8. The high-strength ceramic brick according to claim 5, characterized in that: The raw materials of the glaze layer include, by weight: 20-30 parts of frit, 5-12 parts of kaolin, 1-3 parts of calcined kaolin, 5-10 parts of quartz, 2-8 parts of barium carbonate, 25-38 parts of albite, 5-8 parts of calcite, 3-9 parts of calcined talc, 3-5 parts of zinc oxide, 0.3-0.5 parts of sodium tripolyphosphate, and 0.1-0.2 parts of carboxymethyl cellulose.
9. The high-strength ceramic brick according to claim 8, characterized in that: The chemical components of the glaze layer include, by weight percentage: SiO2 45.5~58.89%, Al2O3 10.5~15.8%, K2O 1.05~1.82%, Na2O3.5~5.44%, CaO5.5~8.85%, MgO 0.5~3.84%, Fe2O3 0.1~0.36%, B2O30.1~3.25%, BaO 5.5~8.67%, ZnO 4.35~6.72%; The chemical components of the frit include, by weight percentage: SiO2 45.5~55.72%, Al2O3 5.0~10.5%, K2O 0.35~3.25%, Na2O3.85~8.45%, CaO7.5~12.5%, MgO 0.59~3.85%, Fe2O3 0.1~0.25%, B2O32.5~5.55%, BaO 7.5~12.55%, ZnO 10.55~15.52%.
10. A method for preparing a high-strength ceramic tile according to any one of claims 5 to 9, characterized in that: include: Mix and grind 20-30 parts of red mud, 0-8 parts of bentonite, 65-70 parts of vanadium-titanium slag, 0-10 parts of ball clay, and 0.3-0.5 parts of green body disintegrator to obtain a formula slurry that meets the preset fineness; The formula slurry is sieved, aged, and impurities removed, and then spray-dried to obtain a powder; The powder is pressed into a shape, dried in a drying kiln to obtain a ceramic body, and a base glaze is applied on the ceramic body to obtain a base glaze layer; Performing inkjet decoration on the base glaze layer to obtain a pattern decoration layer, applying a top glaze on the pattern decoration layer to obtain the top glaze layer and then drying to obtain a glaze blank; The glaze blank is fired at a firing temperature of 1050° C. to 1080° C. and a firing period of 35 to 45 minutes to obtain a high-strength ceramic tile.
Citation Information
Patent Citations
Environment-friendly full body porcelain brick having characteristic of natural granite, and preparation method thereof
CN103553579A
High strength ceramic tile and preparation method thereof
CN109608170A
Low-temperature fast-fired ceramic rock plate and preparation method thereof
CN115010465A
Producing method of black ceramic products materials and products
CN85102464A
Ceramic powder
CN86104984A
Cited By
Crystal flower dry granular glaze, positioning crystal flower rock plate prepared from crystal flower dry granular glaze and preparation method of positioning crystal flower rock plate
CN120349178A
